Predictors of Self-Efficacy in Pregnant Women During the COVID-19 Pandemic - Kusumawardani, Devi Arine; Wahyu Ningtyias, Farida; Al Farizi , Sofia (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2023)
Pregnant women are one of the vulnerable groups affected by the COVID-19 pandemic through limited access and reach to health services, resulting in the adaptation process during pregnancy and increased pregnancy stressors. Self-efficacy is one of the important factors in the ability of pregnant women to cope when experiencing stress and depression during the COVID-19 pandemic. This study aimed to examine the factors that influence the self-efficacy of pregnant women during the COVID-19 pandemic. This is a quantitative study with a cross-sectional design in the working area of ​​the Panti Community Health Center, Jember Regency, from August to October 2021. The research sample was 170 randomly selected using cluster random sampling. The research instrument used the General Self-Efficacy Scale (GSES) to measure self-efficacy and a structured questionnaire to measure the characteristics of the respondents. The results showed that the factors that influenced the self-efficacy of pregnant women during the COVID-19 pandemic were education (p-value = 0.007; OR = 3.852), income (p-value = 0.014; OR = 4.325), and occupation (p-value = 0.014; OR = 4.325), and occupation (p-value = 4.325). value = 0.006; OR = 5.464). And the most influential predictor of pregnant women's self-efficacy during the COVID-19 pandemic was occupation (p-value = 0.002; OR = 6.224). Working mothers tend to have higher adaptability through changing conditions at work as an effort to develop themselves, demands, initiatives, and targets at work to make the right decisions and other stressors at work, so they tend to have higher self-efficacy, be able to solve problems and solve problems challenges well, especially during the COVID-19 pandemic. Conclusion: The predictors that influence pregnant women's self-efficacy during the COVID-19 pandemic are the mother's education, the mother's occupation, and family income. Strengthening cooperation with stakeholders in the region to increase the capability and empowerment of mothers through training to develop the competence of mothers according to mothers’ education and local resources so that they can work in the formal and informal sectors so that mothers' self-efficacy increases.